Adverse Outcomes in Neonates and Children with Pulmonary Artery Hypertension Supported with ECMO. Issue 6 (November 2016) - Nasr, Viviane G.; Faraoni, David; DiNardo, James A.; Thiagarajan, Ravi R.
Abstract : Extracorporeal membrane oxygenation (ECMO) has been increasingly used to rescue neonates and children with cardiac or respiratory failure, and critical illnesses including pulmonary artery hypertension (PAH) unresponsive to conventional therapies. This study assesses mortality and outcomes in neonates and children with PAH supported with ECMO. Neonates and children from the 2012 Health Care Cost and Use Project Kids' Database were identified using ICD-9 codes. Children with congenital heart disease were excluded. Univariate logistic regression was applied to assess the relationship between ECMO and outcomes using matched cohorts for age, elective admission, and Elixhauser comorbidity score. We identified 9, 355 neonates and children with PAH (0.15%). The incidence of ECMO was 1.4% (132/9, 355). After propensity-matched analysis, 130 neonates and children were included in each group. The incidence of mortality was 39% in the group supported with ECMO and 8% in the control group (odds ratio [OR]: 6.98, 95% confidence interval [CI]: 3.43–14.21, p < 0.001). Neonates and children on ECMO had higher odds for acute kidney injury (OR: 2.41, 95% CI: 1.30–4.47, p = 0.005), neurologic complications (OR: 7.11, 95% CI: 1.57–32.18, p = 0.011), sepsis (OR: 2.69, 95% CI: 1.46–4.96, p = 0.002), and thrombotic complications (OR: 2.90, 95% CI: 1.10–7.67, p = 0.032). Neonates and children with PAH supported with ECMO have higher mortality rate and complications compared with matched controls with PAH. Abstract : Supplemental Digital Content is available in the text.